Chapter Esfinge em labirinto de espelhos - Rita, Annabela (Libere carte, 2023)
Reflecting on the history(s) of Europe, this text revisits some of its most strategic bibliographical and aesthetic references for the understanding of the different faces of its identity and its humanist ideals of peace and fraternity. A four-step itinerary: starting with a framework of critical and theoretical essays and its national expression, Portugal, passing through the perspective of the Russia-Ukraine war then leads us to the dream of peace and european fraternity, which David Sassoli defended. An ascensional journey culminating with the tribute to Sassoli.